2018
DOI: 10.1186/s40621-018-0145-z
|View full text |Cite
|
Sign up to set email alerts
|

A quality improvement program in pediatric practices to increase tailored injury prevention counseling and assess self-reported changes made by families

Abstract: BackgroundMany pediatric providers struggle to screen families for the majority of age-appropriate injury risks and educate them when appropriate. Standardized tools have helped physicians provide effective, more purposeful counseling. In this study, pediatricians utilized a standardized, injury prevention screening tool to increase targeted discussions and families were re-screened at subsequent visits to determine changes in their behavior.MethodsPediatric practices, recruited from the Ohio Chapter, American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Putting resources toward the use of a standard injury prevention screening tool has been shown to improve injury prevention in primary care offices. (Gittelman et al 2018) It stands to reason that the ED may be another setting for this type of tool to be utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Putting resources toward the use of a standard injury prevention screening tool has been shown to improve injury prevention in primary care offices. (Gittelman et al 2018) It stands to reason that the ED may be another setting for this type of tool to be utilized.…”
Section: Discussionmentioning
confidence: 99%
“…A hybrid tool to screen for high-risk behaviors, using a previously established IP screening tool (Gittelman et al, 2018) as well as the SEEK screening tool for SDH risks was created (tool available upon request). A test-retest study has shown the injury tool has good reliability (Gittelman et al, 2018). Age-appropriate unintentional injury prevention questions were developed for each age specific category (birth-1 year and 1–5 years).…”
Section: Methodsmentioning
confidence: 99%
“…Although past literature clearly supports that tailored screening by PCPs, with individualized, custom messaging, helps to address specific needs, changes behaviors, and saves health care dollars, this approach is not used consistently by PCP offices (Nansel et al, 2002; Gittelman et al, 2018). By implementing standardized tools into pediatric offices using Quality Improvement (QI) methodology, PCPs are able to screen for and discuss high-risk injury and social topics in a more pertinent and efficient manner (Gittelman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…11 The use of quality improvement (QI) initiatives to provide counseling about other preventive concerns during infancy has encouraged caregivers to practice safer behaviors. 12 Similarly, TSE reduction and cessation counseling by primary care providers (PCPs) may be successful in prompting caregivers to change their tobacco behavior to improve their child’s health. 9,10…”
Section: Introductionmentioning
confidence: 99%